Between two evils: Investors prefer grand corruption! - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2005)
Recent empirical studies claim that, in addition to levels of corruption, investors are deterred by its unpredictability. I claim instead that it is petty corruption that deters investors. I employ seven subcomponents of corruption for a sample of 102 countries that appear in the 2003 Global Competitiveness Report of the WEF. The second principal component of this data depicts a grand, political type, embracing corruption in government policymaking and in judicial decisions as opposed to corruption in public utilities and loan applications. Grand corruption less deters investors because they might feel belonging to an inner circle of insiders that can profit from hidden arrangements. Grand corruption also entails relatively smaller organizational effort.
Keywords: C21; F21; O17; K42; 330; Grand Corruption; Petty Corruption; Extortion; Predictability; Opportunism; Public Utilities; Laws and Policies; Judiciary